Rancang Bangun Mesin Pencacah Plastik Pet dengan Kapasitas 20 Kg/Jam - Prayadi, Aditya Anggara; Arifin, Devi Eka Septiyani; Widiatmoko, Rudy Yuni (Universitas Muria Kudus, 2024)
Shredding is one of the common recycling methods used for plastic waste processing. Along with the development of the era, conventional tools have begun to change to semi-automatic. Therefore, a shredding machine is needed for plastic waste processing with an automatic sensor system to facilitate operation. This design aims to determine the performance of a PET plastic shredding machine with the shredder shredding method. Pahl and Beitz is the method used in making this tool. In accordance with the method applied, the manufacture of the tool starts from planning, concept design, shape design, detailed design, documentation creation and realization of the tool. The testing process is carried out by testing the function of the machine and the function of the automatic sensor. The designed shredder machine has the following specifications: Dimensions of the tool are 950 x 365 x 1060 mm, capacity is 20 kg/hour, 3 phase ½ HP dynamo motor, rotation speed is 70 rpm, number of blades is 14 and material used on the blade is AISI 1080. The test results of this tool show that the tool can work to shred PET plastic, can shred 1 kg of plastic bottles in 2 minutes 45 seconds, the first shredded result is 150 mm maximum smallest size is 16 mm with 3 shredding processes, and can be operated with a sensor control system for the tool's work process. Keywords: shredding machine, garbage, plastic